1979
DOI: 10.1111/j.1399-3054.1979.tb01691.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Endogenous Auxins and Ethylene in the Formation of Adventitious Roots and Hypocotyl Hypertrophy in Flooded Sunflower Plants (Helianthus annuus)

Abstract: The role of ethylene and auxins in flood-induced adventitious root formation and hypocotyl hypertrophy in sunflower {Helianthus annuus L. cv. Russian) plants was studied. Flooding without aeration (F) resulted in a steady increase in ethylene in hypocotyls, and flooding with aeration (FA) caused a transient increase. Low light intensity increased ethylene levels but decreased adventitious root formation. Treatment of shoots with benzyladenine (BA) increased ethylene content in non-flooded (NF) but not in F or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0
4

Year Published

1987
1987
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(46 citation statements)
references
References 31 publications
(31 reference statements)
3
39
0
4
Order By: Relevance
“…During submergence, polar auxin transport is required for AR growth in various species (Visser et al, 1996c;Wample and Reid, 1979;McDonald and Visser, 2003;Xu et al, 2005;Vidoz et al, 2010), including S. dulcamara. According to the gene set enrichment analysis, signaling by auxin was stronger in flooded stem tissue but not significantly induced in primordia.…”
Section: An Essential Role For Auxin In Controlling Ar Activationmentioning
confidence: 99%
“…During submergence, polar auxin transport is required for AR growth in various species (Visser et al, 1996c;Wample and Reid, 1979;McDonald and Visser, 2003;Xu et al, 2005;Vidoz et al, 2010), including S. dulcamara. According to the gene set enrichment analysis, signaling by auxin was stronger in flooded stem tissue but not significantly induced in primordia.…”
Section: An Essential Role For Auxin In Controlling Ar Activationmentioning
confidence: 99%
“…The effects of soil waterlogging in stimulating the production of adventitous roots are well documented (e.g. Gill, 1975;Wample & Reid, 1978;Etherington, 1984); both auxine and ethene have been implicated in initiating adventitious root production (Wample & Reid, 1979;Drew, Jackson & Giffard, 1979;Etherington, 1983). Etherington (1984) showed that the flooding-tolerant species Epilobium hirsutum produced superficial adventitious roots from the stem base in response to soil flooding but the closely related flooding-intolerant species, Chamerion angustifolium, was incapable of initiating these roots.…”
Section: Tissue Mn and Fe Concentrationsmentioning
confidence: 99%
“…Respostas morfológicas como o desenvolvimento de aerênquima, corredores de ar ou espaços aéreos descontínuos, raízes adventícias ou com crescimento diageotrópico e o aumento em superfície (Wample & Reid 1979, Drew et al 1981, Joly 1996, Scatena & Meneses 1996, Santiago & Paoli 2003, constituem-se em respostas expressas por plantas submetidas à hipóxia ou anoxia.…”
Section: Introductionunclassified